Estimating electrification using multi-temporal DMSP/OLS night imagery as proxy measure of human well-being in India - Paul, Arati; Verma, Bhuvanesh; Chakraborty, Debasish (Spatial information research (Online), 2020)
Annual electric power consumption (EPC) measures the electrification rate of a region. In the present study, annual composites of temporal defense meteorological satellite program/operational line-scan system night time light (NTL) imagery is used as a proxy measure for estimating electrification of India. A regression model is obtained using temporal NTL and EPC data of the region for measuring EPC from NTL data. The model is validated by using NTL data of India aquired during 2013 and is observed to be 99% accurate in measuring EPC from NTL data. The NTL data is also used to estimate population of the region and are found to be positively correlated with each other. The present study supports using the NTL data as a proxy measure of human wellbeing.